Exploitation & Social Discrimination Portrayed in the Joker Movie (2019): A Study of Class Analysis - Andi Farid Baharuddin; Amelia Novita Gosal (MediaTor (Jurnal Komunikasi), 2021)
Film is a cultural instrument that can educate people. Through an interesting film, people can activate their intellectualisation in seeing the social situation that occurred in the film. This research examines Joker (2019) a movie containing the discourse ofexploitation  and the social discrimination system related to this era. In this study, researchers elaborate (1) what forms of exploitation and social discrimination does the Joker film have?; and (2)  what are the impacts of the exploitation and social discrimination in the film. The research method used is qualitative. Then in collecting data, the researchers first classify three types of data, namely primary  data, secondary data, and supporting data. These three data are an effort to strengthen the arguments of this study. Furthermore, to analyze the research problem above, the researchers use one of the branches of the sociological theory of Marxism, namely class contradiction analysis and also the theory of communication science called critical discourse analysis to analyse the issue of news media coverage in this film. The results of this study indicate that the form of exploitation and social discrimination in the Joker film is divided into three areas, namely (1) the Health Sector, (2) the Labor Sector and (3) the Media News Sector.